(untitled) (Research, Society and Development, 2022)
Mastery of first aid knowledge is extremely useful and necessary for everyone. In this context, first aid extension projects aim to share technical knowledge with the lay population. This study aimed to evaluate the impact of extension projects and the methods used for teaching this theme. This is a narrative review in which a survey of experience reports published in the PubMed, SciELO, CAPES, and Google Academic databases was carried out. The keywords "first aid", "extension project" and "experience report" were crossed by the Boolean operator AND, considering the particularities of each base. Of the 448 studies found, 432 were excluded for not addressing experience reports, and 16 studies were included. From the information identified, the impact of the projects was organized and analyzed considering as beneficiaries of the action: students involved, participants in the action, university, and society. The impact for the students involves professional and emotional self-realization, and for the participants in the action it is related to training and autonomy to support victims. The university benefits from the closer relationship with the community. And finally, the society benefits from more qualified lay rescuers, longer survival of the injured, accident prevention, and relief of services such as the SAMU. As for the methods, there was a prevalence of the active methodology, especially projects aimed at children. Therefore, it is suggested to explore the extension projects as a strategy for sharing knowledge. Thus, the expansion of these actions can contribute to the improvement of public health.